Calculating government consumption multipliers in New Zealand using an estimated DSGE model - Andrew Binning (New Zealand Government, The Treasury, 2024)
Fiscal multipliers provide a way of quantifying the GDP gain for a given (discretionary) fiscal policy intervention. I compute government consumption multipliers for New Zealand, in normal times and when monetary policy is constrained at the effective lower bound, using an estimated monetary-fiscal dynamic stochastic general equilibrium model. Quantifying the impact of discretionary fiscal policy is important when considering the design of fiscal support packages to offset future economic downturns. I calculate multipliers under a number of different monetary policy assumptions when imposing the lower bound on interest rates. I investigate the range of results implied by the model and the features of the policy and economic environments that lead to larger government consumption multipliers. I find that estimated government consumption multipliers are larger when interest rates are at the lower bound, but still smaller than 1, when entry and exit to the lower bound are determined by both economic conditions and the central bank's reaction function. This implies increases in government consumption crowd out other expenditure. When the central bank can commit to holding interest rates fixed for 2 or more years, independent of economic conditions, government consumption multipliers can exceed 1. Factors that amplify demand shocks are more likely to increase multipliers, especially at the lower bound, though these features may be undesirable for macroeconomic stabilisation more generally. Larger government consumption multipliers are not an end in themselves, rather the size of the multipliers can influence the design of discretionary policy programmes.
Keywords: C11; E52; E62; E63; 330; Government consumption multipliers; monetary policy; effective lower bound; prior predictive analysis; Monte Carlo filtering